Parallel Visions on Media Art- The 6th Seoul International Media Art Biennale - Sunjung Kim; Seoul Museum of Art (Seoul Museum of Art, 2009)
Exhibition Catalog. Texts: Sunjung Kim, Joonsung Yoon, Seungduk Kim, Jaap Guldemond, Franck Gautherot, Sungwon Kim, Ilho Park, Fumihiko Sumitomo, Jen Mizuik, Nicolaus Schafhausen, Jihoon Kim, Clara Kim, Cheolwoong Sim.
English; Korean
Keywords: N4390-5098 Visual Arts- Exhibitions